Ruthenium-Catalyzed Addition of 1,3-Diketones to Terminal Alkynes - Léotard, Benjamin; Fukuyama, Takahide; Higashibeppu, Yuki; Brancour, Célia; Okamoto, Hiromi; Ryu, Ilhyong (Synlett, 2013)
Ruthenium complex [RuCl2(CO)3]2 catalyzes the addition of 1,3-diketones to terminal alkynes. We observed C-addition with acyclic 1,3-diketones, whereas the use of cyclic 1,3-diketones systematically led to O-addition reactions.
Keywords: ruthenium; catalysis; alkynes; 1,3-diketones; vinylation